PEMODELAN DINAMIKA PERKEMBANGAN PERKOTAAN DAN DAYA DUKUNG LAHAN DI KAWASAN CEKUNGAN BANDUNG - Iwan Kustiwan; Almira Ladimananda (Diponegoro University, 2012)
This research of dynamics growth of urban area and land carrying capacity using system dynamics model that can relate all of components complexly has to be done, then we can forecast the behaviour of its variable to make a policy to solve the problem. The components that used in this research are population, land use, flood disaster, and land carrying capacity. Model behaviour shows that the population growth can raise the escalation of built up area, then result the growth of water run off. This escalation of built up area increasing the attraction of its area, so it increase in-migration rate, and increase population so the built up area attains the limit of land carrying capacity at 2020.To anticipate the limitation of land carrying capacity, the policy scenarios were made. The scenarios can prolong the attainment of land carrying capacity limit, developing rural area outside Kawasan Cekungan Bandung and forbid the land use convertion from forest and agriculture land to become built up area, which couldn’t attain but can preserve the green area; and last, the combination of all scenario. The best scenario is the combination of all.